Analysis of Website Vulnerabilities Utilizing OWASP on the Enterpreneurship Locker System - Pamudji, Andre Kurniawan; Setiawan, Florentinus Budi (Soegijapranata Catholic University, 2024)
The government's restrictions on activities during the Covid-19 pandemic resulted in the closure of numerous activities. This has resulted in the closure of numerous businesses, particularly small and medium-sized enterprises, as a result of a lack of customers. Therefore, a new invention was developed in the field of Entrepreneurial Lockers that enables transactions to be conducted without the need for face-to-face interaction and without the use of cash. This innovation entails the development of a website that serves as a digital ordering and payment system. In order to ensure that users feel secure while using the website, it is imperative to assess the website's data security to prevent the occurrence of any unintended events. The OWASP method is employed in this investigation to assess the security of the IoT-based entrepreneurial storage system in order to identify critical security vulnerabilities. The findings indicate that the system has satisfied numerous security standards; however, it necessitates improvement in the areas of access control, framework updates, and logging. This investigation offers suggestions for enhancing the security of data in IoT-based systems.